Hubungan Tingkat Stres dengan Kejadian Penyakit Jantung pada Pasien Diabetes Melitus - Niken Auditya Rahmawati; Okti Sri Purwanti (Malahayati Nursing Journal, 2023)
ABSTRACT Diabetes mellitus (DM) is a non-communicable disease. Usually caused by factors such as obesity, lifestyle changes, age, smoking and stress. Stress can increase blood pressure, when blood pressure is high, blood flow is not smooth so that it can cause interference with the work of the heart or put a person at risk of heart disease. This study aims to analyze the relationship between stress levels and the incidence of heart disease in patients with diabetes mellitus. This type of research is quantitative research using an analytic observational research design with case control. The sample in this study were all patients with diabetes mellitus, who underwent outpatient care at the internal polyclinic and cardiac polyclinic at RSUD Dr. Moewardi Surakarta. With the number of samples in this study were 50 respondents who were divided into 2 groups, namely 25 respondents to the case group and 25 respondents to the control group, the sampling technique used purposive sampling technique. Data collection used the Perceived Stress Scale questionnaire (PSS-10) and medical records. Univariate data analysis in this study used frequency and percentage distributions, while bivariate analysis used the chi-square statistical test with a 95% degree of confidence. The results of this study indicate that there is a relationship between stress levels and the incidence of heart disease in diabetes mellitus patients with a p-value of 0.014 0.05 while the value of OR = 11.769 (CI = 1.319 – 105.008) means that respondents who experiencing severe stress in DM patients have a chance of developing heart disease by 11.769 times greater than respondents who do not experience stress in patients with diabetes mellitus. The suggestion from this study is that it is hoped that this research can add information regarding perceptions and knowledge about the relationship between stress levels and the incidence of heart disease in patients with diabetes mellitus and can also be a reference for further research. Keywords : Diabetes Mellitus, Stress, Heart Disease  ABSTRAK Diabetes mellitus (DM) merupakan penyakit yang tidak menular. Biasanya disebabkan karena faktor seperti obesitas, perubahan gaya hidup, faktor usia, perokok dan stres. Stres dapat meningkatkan tekanan darah, ketika tekanan darah tinggi, maka aliran darah tidak lancar sehingga bisa menumbulkan gangguan pada kerja jantung atau menyebabkan seseorang beresiko terkena penyakit jantung. Penelitian ini bertujuan untuk menganalis hubungan tingkat stres dengan kejadian penyakit jantung pada pasien dibetes melitus. Jenis Penelitian yaitu penelitian kuantitatif dengan menggunakan rancangan penelitian observasional analitik dengan case control. Sampel dalam penelitian ini adalah seluruh pasien diabetes melius, yang menjalani rawat jalan di poli dalam dan poli jantung RSUD Dr. Moewardi Surakarta. Dengan jumlah sampel dalam penelitian ini adalah 50 responden yang dibagi menjadi 2 kelompok, yaitu 25 responden kelompok kasus dan 25 responden kelompok kontrol, teknik pengambilan sampel menggunakan teknik purposive sampling. Pengumpulan data menggunakan kuesioner Perceived Stress Scale (PSS-10) dan rekam medis. Analisa data univariat pada penelitian ini menggunakan distribusi frekuensi dan presentase, sedangkan  analisa bivariat menggunakan uji statistik chi-square dengan derajat kepercayaan 95%. Hasil penelitian ini menunjukkan terdapat hubungan antara tingkat stres dengan kejadian penyakit jantung pada pasien diabetes melitus dengan  nilai p-value 0, 014 0, 05 sedangkan nilai OR = 11, 769 (CI = 1, 319 – 105, 008) artinya responden yang mengalami stres berat pada pasien DM mempunyai peluang terjadinya penyakit jantung sebesar 11, 769 kali lebih besar dibandingkan responden yang tidak mengalami stres pada pasien diabetes melitus. Saran dari penelitian ini adalah diharapkan penelitian ini dapat menambah informasi mengenai persepsi dan pengetahuan tentang hubungan tingkat stres dengan kejadian penyakit jantung pada pasien diabetes melitus dan juga dapat menjadi referensi  bagi penelitian selanjutnya.  Kata Kunci: Diabetes Melitus, Stres, Penyakit Jantung